(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Let denote the number of partitions of where is a positive integer. In this paper, we study Ramanujan’s congruences for the Partition function , especially and respectively and explore the different types of partition congruences along with proof of some partition congruences.